Risk factors for low birth weight in El Jadida province, Morocco. Case-control study - Houda Elfane; Sanaa El-Jamal; Mohamed Mziwira; Imane Barakat; Khadija Sahel; Mohammed El Ayachi; Rekia Belahsen (National Institute of Public Health - National Institute of Hygiene, 2022)
Background. Low birth weight (LBW) is considered to be one of the most important indicators of a newborn's chances of survival, and a major risk of medium- and long-term morbidity. Objective. To identify risk factors associated with low birth weight newborns among pregnant women during childbirth in Moroccan hospital environment with a view to proposing avenues of intervention for its prevention. Material and methods. Data concerning the weight of newborns at birth, nutritional education, pregnancy monitoring and other risk factors, etc. were collected from 312 pregnant women who gave birth in the maternity ward of El-Jadida Provincial Hospital in Morocco. Results. The study identified 156 cases of newborns with LBW and 156 controls of normal-weight newborns. After adjustment for the variables included in the analysis, the determined factors associated with LBW are nutritional education [OR: 6.22 (2.60-14.87), P<0.001], illiterate women [OR: 8.74 (1.65-46.08), P=0.011], insufficient pregnancy monitoring [OR: 5.69 (2.74-11.83),P<0.001], pregnant women with a normal weight [OR: 3.84 (1.73-8.52), P=0.001], lack of psychological support [OR: 3.23 (1.72-6.08), P<0.001] and tiring domestic activity [OR: 2.13 (1.14-3.99), P=0.017]. Conclusion. Promotion of nutrition for pregnant women, proper implementation of maternal health programs and improvement of their social condition are the modifiable factors that should help reduce LBW risk.